2021
DOI: 10.3390/met11020267
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Wire Feeding Speed on Solidification Cracking of CMT Welding for Al-Si Alloys

Abstract: In this work, a welding solidification crack sensitivity test platform was established to study the effect of wire feeding speed (WFS) on solidification crack sensitivity during cold metal transfer (CMT) welding for AA6061 aluminum alloy. The test results show that as the WFS increased from 4 m/min to 5.5 m/min, the sensitivity of the solidification cracks also increased. With a further increase in the value of the WFS, the crack sensitivity decreased and eventually ceased to exist. A new perspective of the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Besides, Huang et al [55] emphasized that increasing the WFS weakens the crack rate while increasing the welding speed increases the crack rate. The same conclusion came with Huang et al [56] as the authors realized that when the WFS exceeded 5.5 m/min, cracks were reduced as the size of the crystal microstructure increased. The mechanical state was stable, which suppressed the occurrence of cracks.…”
Section: Microstructure Analysissupporting
confidence: 77%
“…Besides, Huang et al [55] emphasized that increasing the WFS weakens the crack rate while increasing the welding speed increases the crack rate. The same conclusion came with Huang et al [56] as the authors realized that when the WFS exceeded 5.5 m/min, cracks were reduced as the size of the crystal microstructure increased. The mechanical state was stable, which suppressed the occurrence of cracks.…”
Section: Microstructure Analysissupporting
confidence: 77%
“…Wojciech Stopyra et al [ 19 ] reported that reducing the content of silicon impurities in AA7075 powder could lower sensitivity to solidification cracking in laser powder bed melting. Huang et al [ 20 ] studied the effect of wire feeding speed on the susceptibility to solidification cracking in cold metal transfer (CMT) welding of AA6061 aluminum alloy, and they found that an increase in wire feeding speed first increased the solidification cracking susceptibility of the weld and then decreased it. For the perspective of the effect of the low-heat-input fusion welding method, especially the CMT technique, on the dendritic growth and solidification cracking susceptibility of the weld, more studies on the solidification cracking phenomenon in Al-Cu-Mg-Zn aluminum alloys in CMT welds are required.…”
Section: Introductionmentioning
confidence: 99%